Biogeographic implications of the striking discovery of a 4,000 kilometer disjunct population of the wild potato Solanum morelliforme in South America - Simon, R.; Fuentes, A.F.; Spooner, D.M. (American Society of Plant Taxonomists, 2011)
Solanum morelliforme is an epiphytic wild potato (Solanum section Petota) species widely distributed throughout central Mexico to Honduras. A strikingly disjunct (approximately 4,000 km) population was recently discovered in Bolivia, representing the first record of this species in South America, and the first species in the section growing in both North and Central America and in South America. Our maximum entropy analysis of 19 climatic variables matches the occurrence of the South American locality with great precision. It demonstrates the strong predictive quality of this procedure and suggests similar localities where this species may be found, especially along the eastern slopes of the Andes in the Yungas region of southern Peru and Bolivia. In addition, the presence of S. morelliforme in South America adds to emerging data from yet other sources to question long-held hypotheses of the origin of section Petota in North and Central America.